Well-Being Thresholds and Moral Priority - Adler, Matthew D. (Journal of moral philosophy, 2015)
A welfarist basic minimum is a level of well-being which is the threshold for minimally adequate lives and which serves, in some sense, as a line of moral priority. In his ambitious and philosophically sophisticated book, Dale Dorsey takes on the task of specifying a welfarist basic minimum. His account revolves around the concept of a “project”: a long-term preference that determines the subject’s actions and decisions and provides narrative unity to her life. Dorsey argues that the welfarist basic minimum is a life whose subject achieves at least one valued project. In this review essay, I present three objections to Dorsey’s views. First, his distinction between projects and other preferences is unclear, and his treatment of the problem of adaptive valuations inadequate. Second, it is very implausible that every life with at least one valued project is better than every life with none. Finally, Dorsey’s specific account of moral priority yields the Nauseating Implication (my term) that giving a single below-threshold person a single valued project morally justifies depriving an indefinite number of worse-off individuals of all their non-project goods.